DOES HALLUX VALGUS SURGERY MODIFY THE GAIT PARAMETERS? LITERATURE REVIEW - TRAULLE, MAUDE; MAZEAS, JEAN; SADAKA, JÉRÔME; TOUZARD, RÉMY; TROUSSELIER, MATTHIEU; FORELLI, FLORIAN (International journal of physiotherapy, 2020)
Background: the deformation of the hallux into a valgus constitutes the most frequent deformation of the forefoot and one of the most performed corrective surgeries in the region. This deformation is the cause of many biomechanical disorders and causes gait disturbances. This review aims to analyze the restoration of space-time and kinematic parameters of walking in the aftermath of corrective surgery for hallux valgus.Methods: four studies were analyzed according to the main criteria of walking speed, support time, step length and kinematics of the ankle and foot before and after the intervention.Results: If some of the results obtained in the analyzed works show an improvement of these criteria in post-operative, the subjects having benefited from hallux valgus surgery seem to present some persistent issues in the spatiotemporal and kinematic parameters.Conclusion: This work does not demonstrate the superiority of one surgical technique over another in the recovery of gait. This recovery does not seem absolute, but this review highlights above all the lack of literature on this subject.